The Influencing Factor of Big Data Adoption for Indonesia Open Government - Dyah Puspita Dewi; Bernadus Yuliarto Nugroho (Borong Newinera Publisher, 2024)
The development of digital technology in the industrial revolution 4.0 has made all aspects change, including in the field of government. This is a pressure and challenge for public organizations, as well as an opportunity to reform and adapt through Open Government. Open Government is the starting point of the Big Data era along with the Open Data process as a direct implication of openness in government. Big Data is one of the main elements of Open Government required to be adopted in government business processes. Therefore, the readiness of public organizations in adoption is an important thing to be followed up. This study aims to deliver a literature review the influencing factor of organizations readiness for Big Data adoption with the TOE (Technology, Organization, and Environment) conceptual framework. From the literature review, it is known that for the context of technology, several factors, including advantage, compatibility, complexity, scalability, and information security technology infrastructure influence the readiness in Big Data adoption. From the organizational context, the top management support, financial, human resources are also concluded to have a positive influence. Finally, from the environment point of view, the availability of laws and regulations and the focus on public services are external support systems for Big Data adoption.